Experimental and theoretical studies into the fatigue crack propagation behaviour of the 7075 aluminium-zinc alloy under constant and variable amplitude loading - Kyriacou, S. A (Cranfield University, 1991)
This thesis describes both theoretical and experimental work performed in order to study the fatigue- crack propagation behaviour of the 7075 T7351 Aluminium - Zinc alloy, under constant and variable amplitude loading. For the theoretical aspects of the work. Static, Elastic and Elastic-Plastic Finite Element methods were utilised for the evaluation of residual stresses in the vicinity of the crack tip caused by overloading. The results have demonstrated that the plasticity caused by the loading part of the load cycle induces compressive residual stresses in the vicinity of the crack upon partial and/or full unloading. The experimental work has been carried out aiming to ascertain the constant load amplitude fatigue crack growth behaviour. It has been established that the material does not exhibit a sigmoidal crack growth curve but, one of parabolic like shape. A n empirical crack growth law has been derived to describe the constant load amplitude behaviour. It has been established that overloads cause substantial extension of the total life to failure due to delays caused by overloading. The observed delay increases if block overloads are introduced, and crack arrest is possible to occur . Finally, it is concluded that crack closure is responsible for the observed crack growth rate reductions.